New method for improving solubilization and uptake of lutein and carotenoids in human hepatocellular liver carcinoma (HepG2) cell culture - Lestari, Widya; Jaswir, Irwandi (2014)

(untitled)
A new method to prepare cell culture medium containing high concentrations of lutein and β-carotene was developed. Cellular uptake and antioxidative activity of the carotenoids in HepG2 cells were examined under a wide range of their concentrations.